The Value of Urban Flood Modeling. Issue 1 (9th January 2021) - Rosenzweig, B. R.; Herreros Cantis, P.; Kim, Y.; Cohn, A.; Grove, K.; Brock, J.; Yesuf, J.; Mistry, P.; Welty, C.; McPhearson, T.; Sauer, J.; Chang, H.
Abstract: Floods are important disturbances to urban socio‐eco‐technical systems and their meteorological drivers are projected to increase through the century due to global climate change. Urban flood models are numerical models that have the capability of representing the features of urban ecosystems and the mechanisms of flooding that impact them. They have the potential to play a critical role in flood risk assessment, operational response, and resilience planning, but existing models remain limited in their capability to represent integrated flooding processes in urban areas and provide the credible quantitative information needed to support risk assessment and resilience practice. Research to advance model development, facilitate intensive watershed monitoring for model parameterization and validation, and support collaboration between researchers and practitioners should be prioritized. This will represent a substantial, expensive effort, but will still be of great value as cities are faced with urgent challenges posed by climate change in coming decades. Plain Language Summary: Across the globe, floods in cities cause substantial loss of life, property damage, and other socioeconomic harms. As the global climate changes, meteorological events that cause flooding such as extreme rain, high tides, and coastal storms are projected to become more frequent and severe. Researchers and environmental managers use urban flood models (UFMs)—packages of mathematical equations that can simulate water flow and other flooding processes—to support risk assessment and emergency management and to develop strategies to mitigate future flooding. However, these models are currently limited in their potential to achieve these objectives, despite recent advances in computing and environmental monitoring. We recommend that the research community prioritizes development of improved UFMs, which will involve use of more sophisticated equations and approaches to solve them, intensive monitoring of flooding processes in cities, and development of institutions dedicated to supporting these efforts. Although these initiatives will be resource intensive, the value provided by UFMs and the urgency of urban flooding issues make such an effort worthwhile. Key Points: Urban flood models (UFMs) are critical tools for flood risk assessment, emergency operations, and resilience planning in cities The ultimate goal of UFM development should be the capability for sustained, integrated simulation of urban watersheds A substantial effort will be needed to overcome existing barriers in urban flood modeling, which will be of great value for urban flood resilience